Cross-border mergers and hollowing-out - Oana Secrieru; Marianne Vigneault (Bank of Canada, 2009)
The purpose of our paper is to examine the profitability and social desirability of both domestic and foreign mergers in a location-quantity competition model, where we allow for the possibility of hollowing-out of the target firm. We refer to hollowing-out as the situation where the target firm is shut down following a merger with a domestic or foreign acquirer. Our analysis shows that mergers have ambiguous effects on the profitability of merged firms and on social welfare. Hollowing-out occurs in very few instances in our framework. One such instance is the case of firms located side-by-side in the same cluster and only if it is very costly to transfer the more efficient technology of the acquirer to the domestic target firm. This happens regardless of the origin of the acquirer, domestic or foreign. We also show that there are instances when a cross-border merger with hollowing out is not profitable but it is socially desirable.
Keywords: D43; G34; L41; L13; 330; Economic models; International topics; Market structure and pricing; Fusion; Übernahme; Multinationales Unternehmen; Direktinvestition; Unternehmensentwicklung; Wohlfahrtseffekt; Theorie